The challenge of stickiness in the empowerment of children, women, the elderly and persons with disabilities - Mhd. Sarif, Suhaimi (2019)
This paper postulates that stickiness in terms of inability of practice or policy in implementing decisions and actions for optimum outcomes. Stickiness in the empowerment practice derived from the knowledge, skills, ability, and attitude of individuals or groups in allowing for independent, informed and integrated ability to make decisions and to execute actions. The paper obtained the feedback from policy makers and practitioners for the employment of children, women, the elderly and persons with disabilities. The results of the feedback argued that stickiness is due to rigidity resulted from the highly hierarchical and bureaucratic nature of organization. Future studies should use case study method.